Strategy in practice : a practitioner's guide to strategic thinking - Tovstiga, George (Chichester, West Sussex, UK : Wiley, 2013)
The 2nd edition of Strategy in Practice presents a practitioner focussed approach to strategy. It is increasingly recognised that the ability to adapt classic formulas to changing circumstances and develop fast, sound strategic thinking is what differentiates the successful corporate leader. Developed from experience in industry this successful text will include an instructor site with PowerPoint slides, extra examples and exercises, and links highlighting changing business practice. While rigorously founded on current thinking and theoretical concepts in the field of strategic.
Preface to the first edition -- Preface to the second edition -- Introduction to strategy in practice and strategic thinking -- Articulating the strategic question -- Sense making and strategic insight -- Insight-driven strategic analysis -- Appendices putting strategy to practice -- Appendix A: probing the strategic boundaries of the firm?s unique competing space -- Appendix B: strategy mapping and narrative (based on analysis of the relevant strategy building blocks) -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Strategic planning; Strategic planning; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Strategic planning; Electronic books